Ibn ‘Arabi’s Influence on Ottoman Sufism in Üftade’s Views - Munji, Ahmad; Çeyhan, Semih (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
As a great figure, Ibn ‘Arabi’s thoughts greatly influenced the Sufis who came after him. In fact, some researchers in the field of Sufism say that there are new characteristics that have emerged in the history of Sufism after Ibn ‘Arabi, namely philosophical Sufism. The same influence can also be found in the tradition of Sufism thought on Ottoman, one of them is Üftade. In his work entitled Vâkıât, Üftade mentions Ibn ‘Arabi’s name more than 40 times in various topics of discussion. For example, Üftade claimed that he had met Ibn ‘Arabi several times in his dreams, Ibn ‘Arabi’s level of wilāyah and so on. By using the content analysis method, this paper tried to see how the Üftade’s view of Ibn ‘Arabi’s thoughts actually was, his works and his level of wilāyah among other Sufi figures.